BIPA Learning on Aceh Local Wisdom Through Audiovisual Using the Make E Match Method - Kamaruzzaman Kamaruzzaman; M. Ade Syahputra; Neny Hutagalung; Shalawati Shalawati; Dian Syahfitri (Universitas Negeri Semarang, 2024)
Local wisdom is an idea, knowledge, norms, ethics, and morals that are in accordance with community life and sustainable with the environment. The existence of traditional activities is one part of the symbol of existing local wisdom. The Peseujeuk tradition is a tradition with local wisdom originating from Aceh and is a local wisdom based on existing traditions. This study aims to understand the value of traditional activity videos for BIPA students in terms of the use of audiovisual media with local cultural content. This article discusses the use of traditional activity videos in Aceh as learning media for junior high school BIPA students. The researcher found that the video seemed significant to students' understanding of traditional culture in Aceh, especially the Peuseujeuk tradition through the practice of speaking and writing that they had done in the BIPA class. Although still lacking in terms of affixes, formal and informal contexts, punctuation and conjunctions, and understanding of meaning. This article concludes that based on these findings, further research on this topic is needed to improve BIPA teaching and learning, especially in junior high school classes.